1997
DOI: 10.1111/j.1469-7793.1997.067bi.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Ca2+ Currents through Capsaicin‐ and Proton‐Activated Ion Channels in Rat Dorsal Root Ganglion Neurones

Abstract: Capsaicin and protons cause excitation and sensitization of primary nociceptive afferents. In a subset of dorsal root ganglion (DRG) neurones, which probably represent nociceptive neurones, both capsaicin and protons induce slowly inactivating non‐selective cation currents. Whole‐cell as well as single channel currents activated by these two stimuli share many biophysical and physiological properties in these neurones. This has lead to the suggestion that protons and capsaicin might activate the same ion chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 39 publications
(54 reference statements)
1
34
0
1
Order By: Relevance
“…5). The average reversal potential with 100 mM Ca 2ϩ in eight experiments was 26.6 Ϯ 2.2 mV, indicating the high C a 2ϩ permeability over Na ϩ (P C a /P Na ϭ 2.9) as reported previously (Wood et al, 1988;C aterina et al, 1997;Z eilhofer et al, 1997). These results further suggest that the channel activated by DA is nonselectively permeable to cations, as observed in the CAP-activated channel.…”
Section: Ion Selectivity Of Single-channel Currents Activated By Dasupporting
confidence: 83%
“…5). The average reversal potential with 100 mM Ca 2ϩ in eight experiments was 26.6 Ϯ 2.2 mV, indicating the high C a 2ϩ permeability over Na ϩ (P C a /P Na ϭ 2.9) as reported previously (Wood et al, 1988;C aterina et al, 1997;Z eilhofer et al, 1997). These results further suggest that the channel activated by DA is nonselectively permeable to cations, as observed in the CAP-activated channel.…”
Section: Ion Selectivity Of Single-channel Currents Activated By Dasupporting
confidence: 83%
“…As seen by others, TRPV1 activity increases as acidity of the solution increases up to pH 4.4 (Tominaga et al, 1998). However, unlike progressive activation of TRPV1, extreme acid reduces neural activity in sensory neurons (Steen et al, 1992;Zeilhofer et al, 1997). Thus, the apparent discrepancy between the response profile of TRPV1 and that of sensory neurons to acid suggests an obligatory regulation of TRPV1 by associated proteins.…”
Section: Discussionmentioning
confidence: 86%
“…Acid, one of the major causes of the hyperalgesia induced by inflammation or ischemic injury, is known to excite sensory neurons (Steen et al, 1992;Reeh and Steen, 1996;Zeilhofer et al, 1997). Of the ion channels in sensory neurons that respond to acidic solution (Chen et al, 1998;Reeh and Kress, 2001), TRPV1 is a candidate transducer of acid-induced hyperalgesia (Caterina et al, 1997;Tominaga et al, 1998;Kress and Zeilhofer, 1999;Jung et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Krishtal and Pidoplichko (5) demonstrated that low pH evoked inward currents in rat trigeminal ganglion neurons, and similar observations have been made in rat dorsal root ganglion (DRG) neurons (6)(7)(8) Low pH responses from DRG are characteristically multiphasic in nature, suggesting the existence of distinct types of channel (see, e.g., ref. 7).…”
mentioning
confidence: 69%